ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - M Deni Ferdiansyah; Iqbal, Johandri; Saputra, Ferdyan Wana (LP2M Politeknik Jambi, 2025)
This study aims to analyze the financial performance of oil palm plantation companies listed on the Indonesia Stock Exchange during the period 2020 to 2023. Financial performance is measured using two profitability and liquidity ratios, namely Net Profit Margin (NPM), Return on Investment (ROI), and Return On Equity (ROE) and Current Ratio (CR), Cash Ratio (CSR), Quick Ratio (QR). The method used in this study is quantitative descriptive with a purposive sampling approach, which resulted in four companies as research samples, namely PT Astra Agro Lestari Tbk, PT PP London Sumatera Indonesia Tbk, PT Salim Ivomas Pratama Tbk, and PT Tunas Baru Lampung Tbk. The data used were obtained from the company's financial statements reported in Rupiah. The results of the study indicate that financial ratio analysis provides valuable insights in evaluating company performance and provides information that can be used by management in strategic decision making. This study is expected to contribute to a deeper understanding of the relationship between financial ratios and company financial performance, especially in the context of the oil palm plantation industry.